Generation Z workers on social media: A dramaturgical study of building professional identity online - Narendra Nizam Aldien; Fiqi Pratama Hananta (Digital Theory, Culture & Society, 2025)
This study examines how Generation Z workers form professional identities in the digital work environment using Erving Goffman’s dramaturgical theory. Professional identity is understood as a social process shaped through interaction, self-presentation, and impression control. This research focuses on Generation Z individuals working in digital and social media-based professions. Using a qualitative approach, this study collected data through structured in-depth interviews with five Gen Z informants employed in various digital fields, including content creation, social media management, and online entrepreneurship. Data were analyzed using deductive thematic analysis based on four dramaturgical aspects: front stage, back stage, impression management, and audience segregation. The findings show that Gen Z workers actively and strategically manage their professional identity online. The front stage functions as a space for planned self-branding, while the back stage allows boundary control, emotional regulation, and identity protection. Impression management is used to maintain credibility and career sustainability through various different strategies. Audience segregation enables workers to separate different audience groups across platforms and contexts, helping them balance professional and personal matters. This study demonstrates that professional identity formation among Gen Z digital workers is a layered and reflective process, shaped by structured self- presentation and boundary management in digital spaces.